Toxoplasma gondii infection enhances the kairomonal valence of rat urine - Vasudevan, Anand (2014)
Many animals use chemicals as pheromones to communicate between individuals of the same species, for example to influence mate choice or to assert dominance. Pheromonal communication is an open broadcast system that can be intercepted by unintended receivers such as predators and prey. We have recently reported that male rats infected by the protozoan parasite Toxoplasma gondii become more attractive to female rats. This suggests a facilitatory effect of infection on rat pheromone production. In view of the open nature of pheromonal communication, we postulate that Toxoplasma gondii infection collateraly enhances kairomonal valence of infected rats to their prey. We compared the strength of kairomonal interception by mice when using scent marks from rats infected with Toxoplasma gondii vs. marks from uninfected control rats. Mice exhibited greater avoidance to both fresh urine and aged rat urine marks obtained from infected animals. These results indicate that, at least in some cases, parasitism can result in opportunity costs for hosts by making prey species more averse to them.